Plant Viruses: From Ecology to Control - Castillo, Jesús Navas; Fiallo-Olivé, Elvira (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Plant viruses cause many of the most important diseases threatening crops worldwide. Over the last quarter of a century, an increasing number of plant viruses have emerged in various parts of the world, especially in the tropics and subtropics. As is generally observed for plant viruses, most of the emerging viruses are transmitted horizontally by biological vectors, mainly insects. Reverse genetics using infectious clones-available for many plant viruses-has been used for identification of viral determinants involved in virus-host and virus-vector interactions. Although many studies have identified a number of factors involved in disease development and transmission, the precise mechanisms are unknown for most of the virus-plant-vector combinations. In most cases, the diverse outcomes resulting from virus-virus interactions are poorly understood. Although significant advances have been made towards understand the mechanisms involved in plant resistance to viruses, we are far from being able to apply this knowledge to protect cultivated plants from the all viral threats.The aim of this Special Issue was to provide a platform for researchers interested in plant virology to share their recent results. To achieve this, we invited the plant virology community to submit research articles, short communications and reviews related to the various aspects of plant virology: ecology, virus-plant host interactions, virus-vector interactions, virus-virus interactions, and control strategies. This issue contains some of the best current research in plant virology.